Avaliação da aprendizagem: discursividades de professoras do ensino fundamental na Escola José Monteiro Maia em Castanhal - SILVA, Monique Elane Barroso (2023)
This study analyzes the evaluation of learning in the discourse of Elementary School teachers at José Monteiro Maia Municipal School in Castanhal-PA. The theoretical framework is based on Cipriano Luckesi, Ana Maria Saul, Léa Depresbiteris, Maria Teresa Esteban, Jussara Hoffmann, among others, for discussions on learning assessment. The study has a qualitative approach, bibliographic and field character. For data generation, we used a semi-structured questionnaire with 03 (three) teachers who work in Elementary School, Early Years. For data analysis we used discourse analysis based on Mikhail Bakhtin from the concepts of dialogism and enunciation. The results of the study reveal that the teachers' speeches show a conception of evaluation focused on the perspective of diagnostic, formative, mediating and emancipatory evaluation, developed through different evaluation instruments such as tests, texts, observation sheets, records, portfolios and others, with a view to monitoring and contextualizing the teaching and learning process. We conclude, then, that the teaching and learning process goes beyond a traditional assessment in the classroom, making learning assessment a transformative tool, specific and reflective of the countless situations and challenges that the basic education teacher can experience in the classroom. of class. Being perceptible that the teachers in the pedagogical and school work build the multiplicity of knowledge, through the diagnostic, problematizing and evaluation mediator look.